Balancing public health with economic gains - Long, Chiau Ming *; Paneerselvam, Ganesh Sritheran (Star Media Group Berhad, 2023)
In light of the recent decision by the government to remove nicotine used in ecigarettes and other vaping products from the Poisons List of controlled substances, several precautionary measures can be taken to prevent inappropriate consumption and reduce the potential harm of using these products.